O cotidiano escolar na Revista Brasileira de Estudos Pedagógicos (1984-2014) - Avelino, Wagner Feitosa [UNESP] (2015)
This is a documentary research study, which aims to analyze the approaches presented by several authors, published by the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira - INEP / MEC (Journal of Pedagogical Studies of the National Institute of Educational Studies and Research Teixeira) on the school routine in Brazil, over a period of 30 years. There was a survey of all articles concerning the subject journals between the years 1984-2014. They were analyzed and examined from the volume 65, number 149, May / August 1984 to 95 number 240, May / August 2014. Articles were selected according to their title / subtitle, abstract and keywords that made any reference to the school routine or contained words or phrases such as school. A total of 70 articles were identified in the Research Notes and Studies detected by themes, emphases and standards, in the set of these productions. First, by examining the articles, an analysis of the quantitative and qualitative nature was conducted. Within the quantitative approach, we found that there are strong thematic trends in the first decade of research around the elementary school for teaching-learning processes. The texts were written mostly by women, with the focus on teachers in the classroom. From the quantitative analysis, was created six categories were created entitled: Organization and School Operation; Teaching methods; Teachers; Students; Socio-political aspects and School Routine's Methodology. In a qualitative perspective, considering the school authors that investigated the issue, the main results and considerations of the authors. As qualitative result it was observed that : the construction of standards help to deal with the conflicts ; improve pedagogical practices in teaching and learning; the use of technologies as tools added to the textbook are part of everyday life ; school extras influences interfere with the performance of students and teachers ...